ChemInform Abstract: C(sp3)—H Functionalization of Methyl Azaarenes: A Calcium‐Catalyzed Facile Synthesis of (E)‐2‐Styryl Azaarenes and 2‐Aryl‐1, 3‐bisazaarenes. Issue 15 (24th March 2016) - Yaragorla, Srinivasarao; Singh, Garima; Dada, Ravikrishna
Abstract: A mild, efficient, and sustainable catalytic system for the C(sp 3 )—H functionalization of methyl azaarenes is reported.